Предмет: Алгебра, автор: Elnyrpvl03

3) sin^2a-(1+tg^2a)*cos^2a
4) sin^2a+cos^2a*(1+ctg^2a)*sin^2a

Ответы

Автор ответа: Universalka
0

3)Sin^{2}\alpha-(1+tg^{2}\alpha )*Cos^{2}\alpha=Sin^{2}\alpha-\frac{1}{Cos^{2}\alpha}*Cos^{2}\alpha=Sin^{2}\alpha-1=-Cos^{2}\alpha \\\\4)Sin^{2}\alpha+Cos^{2}\alpha*(1+Ctg^{2}\alpha)*Sin^{2}\alpha=Sin^{2}\alpha+Cos^{2}\alpha*\frac{1}{Sin^{2}\alpha}*Sin^{2}\alpha=Sin^{2}\alpha+Cos^{2}\alpha=1

Похожие вопросы
Предмет: Алгебра, автор: ohanyan028
Предмет: Литература, автор: debi1